Racikan Minuman Jamur Tiram (Pleurotus ostratus) sebagai Peningkat Kesehatan Tubuh - Uce Lestari; Damris Muhammad; Ade Adriadi; Minarni Minarni (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Tanjung Johor sub-district is located in the District of Service of Jambi City and is one of the guided villages of the University of Jambi, which has great natural resource potential. However, the community's livelihoods are still mostly rubber and oil palm farmers. One of the potentials in this village is waste from empty palm oil bunches and used as oyster mushroom farming. The resulting oyster mushroom has not been processed into a health drink, only as a cooking ingredient. The results of guidance and collaboration from Jambi University lecturers, such as introducing the benefits of oyster mushrooms for improving body health in this village, have been carried out, but the production of oyster mushrooms has not been carried out. By seeing this potential came the idea to make a healthy drink from oyster mushrooms. The purpose of this community service activity is to provide selling value for oyster mushrooms from agriculture and post-harvest handling, increase public knowledge about the benefits of oyster mushrooms and maximize human resources in Tanjung Johor village. The method used is oyster mushroom counseling and making health drinks. This activity produces processed products from oyster mushrooms such as health drinks that can increase the selling value of oyster mushrooms and increase the creativity of human resources in Tanjung Johor Village, Pelayangan District Jambi City.